Gestión de talento humano y su incidencia en la atención al cliente en la empresa ICELEC S.A.S., del cantón la Libertad, periodo 2023. - Quimi Salvatierra, Enzo Hernán (2025)
This study examines human resource management and its influence on customer service at ICELEC S.A.S., located in the La Libertad canton, during 2023. The main goal was to determine how practices related to personnel management affect customer satisfaction levels. A descriptive, quantitative-oriented method was used, using questionnaires for both the company's team and customers. The findings indicate that ongoing training and performance appraisal are essential components for optimizing customer service. In addition, it was found that the lack of motivation and internal communication negatively impacts the vision of the service provided by the company. Among the most relevant conclusions, it stands out that the implementation of strategies for the growth of human talent significantly helps to increase customer satisfaction rates and strengthen the competitiveness of the organization. The study proposes the implementation of regular training programs and an incentive system for employees, in addition to promoting a work environment that promotes communication and collaborative work. These measures are essential to achieve a high quality service, improve internal procedures and ensure the sustainability of the company.